Analisis Hubungan Simultan Antara Kepemilikan Manajerial, Risiko, Kebijakan Hutang dan Kebijakan Dividen Dalam Masalah Agensi - Nurfauziah Nurfauziah; D. Agus Harjito; Atik Ringayati (Sinergi: Kajian Bisnis dan Manajemen, 2007)
In a company of go public is often happened the conflict between of stockholder with the manager, where manager act as the function of management and stockholder as function of is ownership. The conflict causes go together the importance difference between manager with the stockholder. Stockholder of course wish the manager work with an eye to maximize the stockholder prosperity. on the contrary, company manager might possibly act do not to maximize the stockholder prosperity but maximizing themselves prosperity. This research test the simultan relation between ownership of manajerial, risk, with the debt and dividen. Sample research as much 69 company, taken with the method of purposive sampling that is only company owning the ownership of incoming manajerial as sampel. To reach the wanted target, this research use the metode two stage least square. Result of research show the existence of consistent relation usher its variable that is negative relation among ownership of manajerial with the risk, debt. Positive relation between ownership of manajerial by dividen, negative relation among risk with the debt and dividen, and also negative relation among dividen with the debt.Keywords: simultant relation, ownership of manajerial, risk, policy of debt and policy of dividend of agency problem